A systematic review of the factors associated with malaria infection among forest rangers - Dapari, Rahmat; Mohd Yusop, Muhamad Zazali Fikri; Chinnasamy, Dharsshini; Zakaria, Nurul Izati; Mohd Shoaib, Siti Munisah; Edros, Mohd Erfan (Public Library of Science, 2024)
Malaria is a vector-borne disease that initially manifests as fever, headache, and chills. The illness could progress to more severe conditions, including lethargy, impaired consciousness, convulsions, shortness of breath, blood in urine, jaundice, and haemorrhage if left untreated. The risk of contracting malaria is considerably heightened in specific occupational settings, particularly among forest rangers, following frequent exposure to natural habitats. Consequently, advancing the understanding of malaria and emphasising how specific occupational environments (including those of forest rangers) contribute to disease risk and management is imperative.